Determinants of Migrants’ Savings in the Host Country: Empirical Evidence of Migrants living in South Africa - Makina, Daniel (Journal of Economics and Behavioral Studies, 2014)
The paper uses a data set of Zimbabwean migrants living in South Africa to investigate the saving behaviour they exhibit in the host country. Having observed that these migrants comprise those that do save in the host country and those that do not save at all, the paper employs a Tobit function that is capable of modelling the savings level as function of migrant characteristics. The results observed are that the level of migrant savings in the host country is positively related to migrant income level, return migration intentions, number of dependents in the host country, remittance level and access to banking services, and is negatively related to the age of the migrant, number of dependents in the home country, migrant length of stay, migrant legal status, and frequency of home visits. Interestingly, the savings behaviour of migrants in the host country mirrors the remittance behaviour in many respects.